0
$\begingroup$

I've been trying to figure out how you solve this question but I just can't seem to understand how to factor

$$56x^4+18x^2-8$$

$\endgroup$
0
10
$\begingroup$

As others have hinted at, start by letting $t=x^2$. Then you get the following: $$ 56x^4+18x^2-8 = 56t^2+18t-8. $$ Now your job is to factor this: \begin{align} 56t^2+18t-8 &= 2(4t-1)(7t+4)\\[0.5em] &= 2(4x^2-1)(7x^2+4)\\[0.5em] &= 2(2x-1)(2x+1)(7x^2+4). \end{align} Thus, we see that $$ 56x^4+18x^2-8 = 2(2x-1)(2x+1)(7x^2+4). $$

$\endgroup$
2
  • 4
    $\begingroup$ Nice substitution and answer! $\endgroup$ – bjd2385 Feb 11 '15 at 0:21
  • 1
    $\begingroup$ That was a very poor approved edit @Shailesh & Leucippus. $\endgroup$ – Daniel W. Farlow Apr 29 '17 at 23:07
4
$\begingroup$

Another way is: Set $t=x^2$. So you have

$56t^2+18t-8=2(28t^2+9t-4)$

$\Delta=9^2+4\cdot28\cdot4=81+448=529$

$t_{1,2}=\frac{-9\pm \sqrt{529}}{56}=\frac{-9\pm 23}{56}$

$t_1=-\frac{32}{56}=-\frac{4}{7}$ $t_2=\frac{14}{56}=\frac{1}{4}$

so

$56(t-\frac{1}{4})(t+\frac{4}{7})$

$56(x^2-\frac{1}{4})(x^2+\frac{4}{7})=$

$56(x-\frac{1}{2})(x+\frac{1}{2})(x^2+\frac{4}{7})=$

$2(2x+1)(2x-1)(7x^2+4)$

$\endgroup$
0
2
$\begingroup$

Hint: Let $y = x^2$ and then factor.

$\endgroup$
2
  • $\begingroup$ It's a factoring question, what you're given is what you solve for, there is no Y therefore I cannot factor for Y. $\endgroup$ – Dunja Elez Feb 10 '15 at 23:26
  • 2
    $\begingroup$ @Dunja Aaron/lhf are telling you to notice that you can solve $56(x^2)^2+18x^2-8$ for the value of $x^2$. $\endgroup$ – anon Feb 10 '15 at 23:56
1
$\begingroup$

Hint: Set $u=x^2$. Factor the resulting quadratic in $u$.

$\endgroup$
1
  • 3
    $\begingroup$ (and then factor each of the pieces in $x$) $\endgroup$ – oxeimon Feb 10 '15 at 23:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.